Physicochemical properties of Josapine pineapple (Ananas comosus) - Mohd Rosdan, Faridatul Ain; Yusof, Yus Aniza; Aziz, Mohammad Gulzarul; Chin, Nyuk Ling; Mohd Amin, Nor Amaiza; Mohd Ghazali, Hasanah; Chong, Pik Han (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Pineapple pulp and its freeze-dried powder prepared from Josapine pineapple were assessed for physicochemical properties such as colour values (L*, a*, and b*), titratable acidity (TA), total soluble solids (TSS), proximate composition (moisture, protein, ash, fiber and fat content), water activity (Aw), pH, and also the sensory evaluation. Data obtained were analysed using ANOVA where the values of p<0.05 were define as significant. Moisture content, TSS and colour measurement showed a significant different p(<0.05) where; moisture content (pulp) in the range of 87.90 – 91.17 %, moisture content (powder); 1.98 – 2.92 %; TSS (pulp): 18.74 – 22.81 °Brix, TSS (powder): 31.76 – 35.30 °Brix; colour measurement (pulp): L* (51.11-75.27), a* (3.35-3.93), colour measurement (powder): L* (37.59 – 49.63), a* (2.91 – 6.47). All the range of values is throughout all the treatments which can be used to discriminate between pulp and freeze-dried powder, whilst TA, TSS, pH and sensory evaluation results can be used to discriminate between freeze-dried powders prepared using maltodextrin and the one with addition of sugar.